IRF4b and IRF8 Negatively Regulate RLR-Mediated NF-κB Signaling by Targeting MITA for Degradation in Teleost Fish - Yan, Xiaolong; Zhao, Xueyan; Zhou, Ming; Sun, Yuena; Xu, Tianjun (Frontiers in Immunology, 2022)
MITA is a significant signal adaptor in the RLRs signaling pathway and plays an important role in the innate immune system. As a transcription factor, NF-κB can be available in many signaling pathways including the RLRs signaling pathway and relative to biological processes like immune responses. In this study, it is determined that IRF4b and IRF8 can have a negative effect on NF-κB signaling pathway mediated by MITA in fish. Firstly, it is found that IRF4b and IRF8 have an inhibitory function on MITA-mediated NF-κB signaling pathway. It is interesting for IRF4b and IRF8 to make the similar functions that MITA is precisely down-regulated and the degradation of MITA is through the ubiquitin-proteasome pathway. IRF is taken as the core domain of IRF4b or IRF8 for the down-regulation to MITA. This study provides data on MITA-mediated NF-κB signaling pathway in teleost fish and provides new insights into the regulatory mechanism in fish immune system.